Dysregulated expression of CD66a (BGP, C-CAM), an adhesion molecule of the CEA family, in endometrial cancer. - Bamberger, A. M. (1998)
CD66a (BGP, C-CAM) is an adhesion molecule of the carcinoembryonic antigen family that has been shown to be down-regulated in colorectal, prostate, and breast cancers. The purpose of the present study was to determine its expression pattern in the normal human endometrium and in endometrial neoplasia. For this purpose, we performed immunohistochemistry using the 4D1/C2 monoclonal antibody on a series of 24 normal endometrial samples and 47 endometrial carcinomas. Strong CD66a expression was observed in glandular and luminal epithelial cells of the normal endometrium with a consistent localization at the apical poles of these cells throughout the cycle. In late secretory (premenstrual) phase, loss of cellular polarity resulted in a membranous expression pattern in some glandular cells. In the analyzed tumor samples increasing areas with a complete loss of expression were observed with increasing malignancy grade. The apical expression pattern of the normal epithelium was changed to a membranous all-around pattern in 55% of the tumors, mostly in solid areas. This change correlated with malignancy grade and could be observed in 3 of 15 G1 tumors, 4 of 12 G2 tumors, 11 of 12 G3 tumors, and 8 of 8 serous-papillary carcinomas. Areas with membranous expression pattern could be observed along with areas with a normal apical expression pattern in lower grade carcinomas and with areas with complete loss of expression in high grade tumors. Northern blot analysis showed a loss of mRNA expression in tumor samples and HEC-1B endometrial adenocarcinoma cells. Loss of protein expression in the tumor samples was also observed by Western blot. In conclusion, CD66a protein expression is dysregulated in endometrial carcinomas, showing reduction or loss of expression with increasing malignancy grade and a change from the apical to a membranous localization.